The future exacerbation and mortality of different inhalation therapies among patients with chronic obstructive pulmonary disease in various GOLD groups: a focus on the GOLD 2017 and GOLD 2023 reports - Qing Song; Wei Cheng; Cong Liu; Xueshan Li; Ling Lin; Yating Peng; Yuqin Zeng; Rong Yi; Yi Liu; Xin Li; Yan Chen; Shan Cai; et al. (Therapeutic Advances in Respiratory Disease, 2023)
Background: The Global Initiative for Chronic Obstructive Lung Disease (GOLD) 2023 report revised the combined assessment, merged the C and D groups into the E group, and revised the initial inhalation therapy recommendation. Objectives: This study aimed to analyze the future exacerbation and mortality of different inhalation therapies among patients with chronic obstructive pulmonary disease (COPD) in various groups based on the GOLD 2017 and GOLD 2023 reports. Design: This is a multicenter and retrospective study. Methods: Stable COPD patients from the database setup by 12 hospitals were enrolled. The patients were divided into Groups A, B, C, D, and E according to the GOLD 2017 and GOLD 2023 reports. Then, the patients were classified into long-acting muscarinic antagonist (LAMA), long-acting β2-agonist (LABA) + inhaled corticosteroid (ICS), LABA + LAMA, and LABA + LAMA + ICS subgroups. Data on exacerbation and death during 1 year of follow-up were collected. Results: A total of 4623 patients were classified into Group A (15.0%), Group B (37.8%), Group C (7.3%), Group D (39.9%), and Group E (47.2%). The exacerbation, frequent exacerbation, and mortality showed no differences between different inhalation therapies in Groups A and C. Patients treated with LABA + LAMA or LABA + LAMA + ICS had a lower incidence of exacerbation and frequent exacerbation than patients treated with LAMA or LABA + ICS in Groups B, D, and E. The exacerbation, frequent exacerbation, and mortality showed no differences between different inhalation therapies after combining Groups A with C. Conclusion: Patients in Group A should be recommended to undergo mono-LAMA, while patients in Groups B and E should be recommended treatment with LABA + LAMA, which is consistent with the GOLD 2023 report. However, it is worth considering merging Groups A and C into a single group and recommending mono-LAMA as the initial inhalation therapy.